2004
DOI: 10.1007/s11745-004-1236-0
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect of α‐linolenic acid on PUFA conversion, bioavailability, and storage in the hamster

Abstract: If an increased consumption of alpha-linolenic acid (ALA) is to be promoted in parallel with that of n-3 long-chain-rich food, it is necessary to consider to what extent dietary ALA can be absorbed, transported, stored, and converted into long-chain derivatives. We investigated these processes in male hamsters, over a broad range of supply as linseed oil (0.37, 3.5, 6.9, and 14.6% energy). Linoleic acid (LA) was kept constant (8.5% energy), and the LA/ALA ratio was varied from 22.5 to 0.6. The apparent absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 43 publications
7
37
1
3
Order By: Relevance
“…Under these conditions, the only variable was the oleic/ALA ratio, and a previous study showed that ALA transport, storage, and conversion into EPA were strictly proportional to dietary ALA intake (30). By contrast, in the present study, increasing dietary ALA did not result in a linear dose-response of all lipid parameters that were affected in different ways: (i) plasma TG and cholesterol responded to the lowest ALA supply (10% FA, 3.6% total energy) and were not further affected by higher doses; (ii) the activity of lipogenic enzymes (ACC and ME) was negatively correlated to dietary ALA intake; (iii) liver TC, faecal excretion of TC and BA, and BA profiles varied only with very high ALA intakes.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Under these conditions, the only variable was the oleic/ALA ratio, and a previous study showed that ALA transport, storage, and conversion into EPA were strictly proportional to dietary ALA intake (30). By contrast, in the present study, increasing dietary ALA did not result in a linear dose-response of all lipid parameters that were affected in different ways: (i) plasma TG and cholesterol responded to the lowest ALA supply (10% FA, 3.6% total energy) and were not further affected by higher doses; (ii) the activity of lipogenic enzymes (ACC and ME) was negatively correlated to dietary ALA intake; (iii) liver TC, faecal excretion of TC and BA, and BA profiles varied only with very high ALA intakes.…”
Section: Resultsmentioning
confidence: 98%
“…Fatty acid methyl esters (FAME) were analysed by GLC with a chromatograph (Fisons 8000, Thermo products, Les Ulis, France) under the conditions described by Morise et al [30]. Saponification of lipids was performed at 85 °C with ammonia (2 N) in ethanol, then neutral sterols (containing cholesterol and phytosterols) were extracted with petroleum ether, using 14 Ccholesterol (Perkin Elmer Life Sciences, Boston, USA, 45 mCi·mmol -1 ) as a marker.…”
Section: Dietary Lipidsmentioning
confidence: 99%
See 3 more Smart Citations